RESTORATIVE EFFECTS OF ZINGIBER OFFICINALE ON ARSENIC-INDUCED GENOTOXIC EFFECTS IN CHROMOSOMAL STRUCTURE OF MICE - Sharma, Suman; Gill, Anjali Singh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study investigated the antigenotoxic effect of Zingiber officinale (Ginger) on arsenic-induced genotoxic effects in chromosome structure of Swiss albino mice. Methods: Albino mice were divided into four groups: Group I was kept as control, Group II was administrated an oral dose of arsenic trioxide 5 mg/kg bw for 15 days, Group III was given an oral dose of arsenic trioxide 5 mg/kg bw followed by 20 mg/kg bw of ginger orally, and Group IV was administered with 20 mg/kg bw of ginger orally for 15 days and kept as positive control. The autopsies were done from all the groups on 15-day post-treatment, and bone marrow was removed for chromosomal study and for calculating the frequency of micronuclei (MN). Results: It is concluded from this study that long-term arsenic exposure causes chromosomal anomalies, for example, breaks, gaps, rings, stretching, and stickiness which leads to the fragmentation of chromosomes and increases the frequency of MN. Conclusion: The administration of ginger showed modulatory effects against arsenic-induced genotoxicity.